#refugeesnotwelcome: Anti-refugee discourse on Twitter. Issue 5 (October 2017) - Kreis, Ramona
In this study, I examine the online discourse of the European refugee crisis on the micro-blogging platform, Twitter. Specifically, I analyze 100 tweets that include #refugeesnotwelcome, and explore how this hashtag is used to express negative feelings, beliefs and ideologies toward refugees and (im)migrants in Europe. Guided by critical discourse studies, I focus on Twitter users' discursive strategies as well as form and function of semiotic resources and multimodality. Twitter users who include this particular hashtag use a rhetoric of inclusion and exclusion to depict refugees as unwanted, criminal outsiders. These tendencies align with current trends in Europe where nationalist-conservative and xenophobic right-wing groups gain power and establish a socially accepted discourse of racism.